2016
DOI: 10.1123/ijspp.2015-0223
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Differential Ratings of Perceived Exertion as Measures of Internal Load

Abstract: and leg exertion (RPE-L) immediately upon exercise termination (RPE-B0, RPE-L0) and 30-minutes post-exercise (RPE-B30, RPE-L30). Data were analysed using magnitude-based inferences. Results: There were clear between-protocol differences for V O2max (Cycle 46.5 ± 6.3 vs Treadmill 51.0 ± 5.1 ml·kg -1 ·min -1 , mean difference -9.2%; ±90% confidence limits 3.7%), HRmax (185 ± 13 vs 197 ± 8 b·min -1 , -6.0%; ±1.7%), B[La]peak (9.7 ± 2.1 vs 8.5 ± 2.0 mmol·L -1 , 15%; ±10%) and ΔCMJH (-7.1 ± 4.2 vs 0.6 ± 3.6 cm, -23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 8 publications
5
56
0
4
Order By: Relevance
“…Consistent with previous studies, we found peripheral ratings of exertion to be higher than central ratings (Pandolf et al, 1975; Green et al, 2009; Borg et al, 2010; McLaren et al, 2016). The magnitude of the difference in the two perceptual responses was small, which is consistent with recent reports in athletic populations (McLaren et al, 2016). This finding helps to explain the lower compliance for RPE-C as our high-intensity criterion was the same for both measures of RPE.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we found peripheral ratings of exertion to be higher than central ratings (Pandolf et al, 1975; Green et al, 2009; Borg et al, 2010; McLaren et al, 2016). The magnitude of the difference in the two perceptual responses was small, which is consistent with recent reports in athletic populations (McLaren et al, 2016). This finding helps to explain the lower compliance for RPE-C as our high-intensity criterion was the same for both measures of RPE.…”
Section: Discussionsupporting
confidence: 92%
“…An example would be to ask athletes to be specific about how much their ‘legs’ were affected, i.e., rate of perceived leg-muscle exertion (RPE-L) [23, 28]. This differentiation in physiological and biomechanical internal load enables monitoring of both central [breathlessness (RPE-B), e.g., uptake and transport of oxygen, central nervous system] and peripheral (RPE-L, e.g., neuromuscular, musculoskeletal, and muscle metabolite characteristics) exertion in team sport athletes [85]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure data consistency, exercise HR was recorded using the same HR monitors across the tests and playing conditions. To evaluate player's general and differential fatigue (ie, central and peripheral), the rating of perceived exertion (RPE) as global (RPE G ), cardiorespiratory (RPE CR ), and muscular (RPE M ) scores was assessed after the Match and maximal tests, using the CR10 Börg scale …”
Section: Methodsmentioning
confidence: 99%
“…To evaluate player's general and differential fatigue (ie, central and peripheral), the rating of perceived exertion (RPE) as global (RPE G ), cardiorespiratory (RPE CR ), and muscular (RPE M ) scores was assessed after the Match and maximal tests, using the CR10 Börg scale. 18 The HR max was assumed as the highest value obtained across these testing protocols and settings. For each testing procedure, players' HR max achievement was reported as the absolute and relative number of players reaching their individual HR max (ie, frequency of attainment of HR max ).…”
Section: Methodsmentioning
confidence: 99%